Sulfur partitioning between glutathione and protein synthesis determines plant growth - Speiser, Anna; Silbermann, Marleen; Dong, Yihan; Haberland, Stefan; Uslu, Veli Vural; Wang, Shanshan; Bangash, Sajid A. K.; Reichelt, Michael; Meyer, Andreas J.; Wirtz, Markus; Hell, Rüdiger (Plant physiology, 2018)
Photoautotrophic organisms must efficiently allocate their resources between stress-response pathways and growth-promoting pathways to be successful in a constantly changing environment. In this study, we addressed the coordination of sulfur flux between the biosynthesis of the reactive oxygen species scavenger glutathione (GSH) and protein translation as one example of a central resource allocation switch. We crossed the Arabidopsis (Arabidopsis thaliana) GSH synthesis-depleted cadmium-sensitive cad2-1 mutant, which lacks glutamate cysteine (Cys) ligase, into the sulfite reductase sir1-1 mutant, which suffers from a significantly decreased flux of sulfur into Cys and, consequently, is retarded in growth. Surprisingly, depletion of GSH synthesis promoted the growth of the sir1-1 cad2-1 double mutant (s1c2) when compared with sir1-1. Determination of GSH levels and in vivo live-cell imaging of the reduction-oxidation-sensitive green fluorescent protein sensor demonstrated significant oxidation of the plastidic GSH redox potential in cad2-1 and s1c2. This oxidized GSH redox potential aligned with significant activation of plastid-localized sulfate reduction and a significantly higher flux of sulfur into proteins. The specific activation of the serine/threonine sensor kinase Target of Rapamycin (TOR) in cad2-1 and s1c2 was the trigger for reallocation of Cys from GSH biosynthesis into protein translation. Activation of TOR in s1c2 enhanced ribosome abundance and partially rescued the decreased meristematic activity observed in sir1-1 mutants. Therefore, we found that the coordination of sulfur flux between GSH biosynthesis and protein translation determines growth via the regulation of TOR.